PENGARUH REFORMASI BIROKRASI TERHADAP KINERJA PEGAWAI DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN SITUBONDO - Yuni Dwi Lestari; Senain Senain (ACTON, 2018)
The purpose of this study was to determine the effect of bureaucratic reform on employee performance at the Situbondo Regency Population and Civil Registration Service. This research paradigm is quantitative with descriptive type and uses survey methods. The population and sample in the study were 34 employees in the Population and Civil Disability Office of Situbondo Regency. The variables to be examined are the independent variable is Bureaucratic Reform (X) and the dependent variable is Employee Performance (Y). The analytical method used is Validity Test, Reliability Test, Simple Regression Analysis, Partial Test (t-test) and Determination Coefficient Test (R2). The results showed that there was a positive and significant influence between bureaucratic reform on employee performance by 15% and the remaining 85% influenced by other variables not included in this study.